Targeting High Ability Entrepreneurs: Replication and Heterogeneity by Gender of Hussam, Rigol and Roth (2022) - Isabella Masetto; Diego Ubfal (Institute for Replication (I4R), 2023)
Hussam et al. (2022a) use a cash grant experiment in India to demonstrate that community knowledge can help target high-growth microentrepreneurs. In their preferred specification, the authors find that the average marginal return to the grant is 9.4 percent per month, while estimated returns for entrepreneurs reported by peers to be in the top third of the community are between 24 percent and 30 percent. First, we reproduce the paper's main findings and uncover one minor coding error, which affects the estimates for one of the main tables but does not change the overall conclusions of the paper. Second, we test the robustness of the results to: (1) different treatment of outliers, (2) dropping surveyor and survey month fixed effects, and (3) using quartiles instead of terciles for grouping the ranking of entrepreneurs. The paper's results are robust to these robustness checks. Finally, we test heterogeneity of results by gender, which was not reported in the original study.
Keywords: 330